Feeding Formulations Made From Raw Seaweed Flour Eucheuma Cottonii Results Of Fermentation With Various Concentrations Of Em-4 In Cultivation Of Tila Fish (Oreochromis niloticus) - Safitri, Mia; Lumbessy, Salnida Yuniarti; Lestari, Dewi Putri (Program Studi Budidaya Perairan Universitas Mataram, 2025)
Tilapia fish (Oreochromis niloticus) is a freshwater fish that has very high economic value. An important factor in cultivating tilapia is feed nutrition. The nutritional content needed to meet fish needs consists of protein, fat, carbohydrates, minerals and vitamins. . The quality of feed depends on the type of raw material used to meet the nutritional needs of fish. One of the raw materials that has the potential to be used as raw material for fish feed is Eucheuma cottoni seaweed. which contains minerals such as calcium, magnesium, sodium, iron, zinc, iodine, as well as vitamin C and vitamin E. However, the problem with seaweed is the high carbohydrate content which causes the high fiber content. One way to reduce the fiber content is through the fermentation process. The success of the fermentation process is also determined by the type of fermenter used. Fermenter, EM-4 (Effective Microorganisms). is one of the fermenters that is widely used because it contains microorganisms. This research used tilapia fish seeds, carried out for 50 days in the laboratory. The method used in this research was a completely randomized design (CRD) method using 4 treatments and 3 repetitions, namely treatment P1: without the addition of EM-4 (control), treatment P2: addition of E. cottonii seaweed with 2 ml EM-4, P3: addition of E. cottonii seaweed with 4 ml EM-4, P4: addition of E. cottonii seaweed with 6 ml EM-4. The parameters tested in this study were absolute weight growth, specific growth rate, absolute length, feed conversion ratio, feed utilization efficiency and survival of tilapia and water quality. Data were analyzed using Analysis of Variance (ANOVA) at a confidence level of 95%. The research results showed that the addition of E.cottonii seaweed flour could increase the absolute weight, absolute length and survival of tilapia with the average absolute weight of tilapia during rearing ranging from 7.41 Ì¶ 7.65 g, absolute length ranging from 4.95 Ì¶ 5.1 cm, The specific growth rate ranges between 2,147 Ì¶ 2,203 %/day, with a feed conversion ratio ranging between 1.31 Ì¶ 1.57 and feed utilization efficiency ranging between 75.97 Ì¶ 81.09 %, and tilapia survival ranging between 53.3 Ì¶ 76.7 %. Water quality during maintenance is still within the normal range for tilapia cultivation, namely temperature ranging between 27.2 Ì¶ 29.7 ÂºC, pH ranging between 7.4 Ì¶ 8.6 and DO ranging between 5.5 Ì¶ 6.6 mg/l.